EVALUASI PERALATAN WATER DEGASSING BOOT PV-950 DI UNIT PENGOLAHAN AIR CENTRAL PROCESSING AREA SUKOWATI - Arif Nurrahman; Ghafar Hamid Abdillah (Nusantara Hasana Journal, 2023)
PT Pertamina EP Asset 4 Field Sukowati, which is a company engaged in the upstream sector of oil and gas. One of the processing units in the Sukowati Central Processing Area is the production water treatment unit. This production water is water that is included in the crude oil separation process. The produced water must go through water vapour separation before being stored in the storage tank to prevent overpressure. This research uses the ratio analysis method of the area of water vapour separation from the produced water. Furthermore, an evaluation of the water-degassing boot and troubleshooting related to corrosion and the presence of a flame arrester as a safety device was conducted. The water-degassing boot is a special column designed to separate associated gases from liquid crude oil. It is equipped with a mist eliminator to ensure that no water vapour is included. The performance evaluation of the tool is done by calculating the separation area ratio (Rm) value. The calculation results show that the device has an Rm value of 3.9801, which indicates good separation performance. Based on the results of calculations and observations, it can be concluded that the water-degassing boot at PT Pertamina EP Asset 4 Field Sukowati has good performance in separating water vapour from produced water before it is stored in the tank.